On the Job or in the Joint: Criminal Justice Contact and Employment Outcomes - Fernandes, April D. (Crime & delinquency, 2020)
Existing research has shown that the rise of incarceration had a substantial effect on the stabilizing forces of employment. The conditions and circumstances that render felony imprisonment impactful are also present for less severe points of contact. Using longitudinal data from the National Longitudinal Study of Youth, 1997 (NLSY97), this project explores the effects of the continuum of contact, namely, an arrest, conviction, and jail sentence, on employment stability and wages. Results show that the consistency of employment is detrimentally affected by all points of low-level contact, with an added penalty for African Americans. These results point to the salience of exploring all levels of contact to fully ascertain how the criminal justice system can increase stratification and occupational inequality.